CHARECTERIZATION OF ENTEROTOXIN PRODUCED BY LOCAL ISOLATE OF YERSINIA ENTEROCOLITICA AND STUDY OF THE INHIBITORY EFFECT OF ERUCA SATIVA ON ITS ACTIVITY - Flayyih, May (Iraqi Journal of Science, 2024)
Enterotoxin produced by local isolate of Yersinia enterocolitica was purifiedfrom the culture supernatant .The purification procedure involved precipitation byammonium sulfate (50% saturation ) and analyzed by sodium dodecyl sulfate- polyacrylamide gel electrophoresis (SDS-PAGE), ( 159.4) fold purification was achievedwith yield of (17.9)%. The molecular weight of purified enterotoxin was 11,000Dalton.The purified enterotoxin was heat stable at 100 оC for 15 min, and the activity waslost after incubation with 3mM dithiotheritol as reducing agent. Enterotoxic activityof Y. enterocolitica was neutralized by antiserum from mice immunized with thepurified enterotoxin .The inhibitory activity of Eruca sativa extracts was tested, bothseed and leave extracts had inhibitory activity in a dose- dependent manner.